The Role Of Community In The Maintenance And Preservation Of Coral Reefs In Ujung Genteng, Sukabumi - Adrie Frans Assa; Gidion P. Adirinekso (Jurnal Manajemen Indonesia, 2022)
Coral reefs have an important role in the economic aspects of coastal communities in the Ujung Genteng, Sukabumi which depends on shallow waters. Increased human activity around the coast has an impact on coral reef ecosystems which are easily fragile by natural and non-natural factors. To prevent damage of coral reefs that have an impact on people's livelihoods, the community has carried out conservation efforts by involving various parties in Ujung Genteng. This study examines the role of the community in the maintenance and preservation of coral reefs. This study uses a qualitative design with a case study approach. Based on the research results, it is found that the community has a role in the preservation and maintenance of the marine environment, especially the coral reef ecosystem, in collaboration with related agencies and CSR and involving the local community directly as well. Community involvement in the process of maintaining and preserving coral reefs is also intended to increase the welfare of local communities that work as fishermen